A study of the molecular variation between orbivirus proteins - Whistler, Toni (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1985)
The aim of this study was to initiate a structural analysis of the capsid polypeptides from several serotypes of bluetongue virus in order to provide insight into the relatedness and possible origins of the different serotypes. Tryptic peptide mapping of Â¹Â²â µI-labelled group antigen by ion exchange chromatography was used to assess the structural relatedness of seven BTV serotypes from Southern Africa, North America and Australia. Each serotype had several tyrosine containing tryptic peptides which were unique, but approximately 35% of the peptides analyzed were found to be highly conserved between all 7 serotypes. BTV-20 appeared to be closely related to BTV-B and these two serotypes with BTV-4 and BTV-17 appeared to form a closely knit central cluster.,KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Proteins -- Analysis; Polypeptides; Bluetongue virus; Orbivirus infections